Expressive timing in choir: An interactive study between choristers and conductor - Ordás, Manuel Alejandro (2018)
In traditional choral practice it would seem that the chorister’s action is an embodied way of responding to the conductor's gestures and being with the other from a second-person perspective (Gomila, 2003). From a conductor-choir interactive perspective, the choir is understood as a set of individuals who are also in interaction and not as a uniform group subordinated to the conductor. Clayton (2013) proposes three levels of musical entrainment between individuals: intra-individual, intra-group and inter-group, to describe the temporal interactions between singers in choral practice. A multimodal analysis (conductor movement and choir members' asynchronies) is presented to investigate the role of inter- and intra-individual variability in supporting collective (choir) musical performance.